2005
DOI: 10.1590/s1517-83822005000100005
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Aspergillus ochraceus, A. carbonarius and A. niger on culture media at different water activities and temperatures

Abstract: The objective of this paper was to determine the influence of three culture media with different water activities, times of incubation and temperatures on the growth of A. ochraceus, A. carbonarius and A. niger. Spores of A. ochraceus, A. carbonarius and A. niger were inoculated onto three culture media: Czapeck Yeast extract Agar (CYA), Dichloran 18% Glycerol Agar (DG18) and Malt Yeast extract 40% Glucose Agar (MY40G). The plates were incubated at five different temperatures (8, 25, 30, 35 and 41ºC). The grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 15 publications
7
25
1
2
Order By: Relevance
“…Many researchers support our results; Subbarao et al (1993);Alwakeel (2008) and Nawar (2008) found that the optimum growth temperature for the A. niger was 30°C. Present result do not support the statement of Palacios-Cabrera et al (2005) who showed that A. niger prefers to grow at temperatures higher than 30°C. In addition, Al-Garni et al (2007) found that 25°C was the optimum linear growth for A. niger.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Many researchers support our results; Subbarao et al (1993);Alwakeel (2008) and Nawar (2008) found that the optimum growth temperature for the A. niger was 30°C. Present result do not support the statement of Palacios-Cabrera et al (2005) who showed that A. niger prefers to grow at temperatures higher than 30°C. In addition, Al-Garni et al (2007) found that 25°C was the optimum linear growth for A. niger.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar result was obtained by (Palacios-Cabrera et al, 2005) they found that the A. niger was able to grow in all culture media, Czapeck Yeast extract Agar (GYA), Dichloran 18% Glycerol Agar and Malt Yeast extract 40% Glucose Agar (MY40G).…”
Section: Discussionsupporting
confidence: 82%
“…Other studies suggest that the optimal temperature for A. carbonarius growth is between 25 and 30°C (Leong et al, 2004) or between 25 and 35°C depending on the isolate and the growth susbtrate used (Mitchell et al, 2003). Studies conducted by Palacios-Cabrera et al (2005) demonstrated that temperatures between 25 and 30°C favored A. ochraceus colony diameter growth, on the other hand, slower growth could be observed at 35°C and total inhibition at 41°C in all the tested culture media. Substrates directly affect fungal development.…”
Section: Discussionmentioning
confidence: 90%
“…Fungal growth and consequent OTA production are determined by a wide range of parameters, classified as physical, chemical and biological, as well as by interactions encompassing these factors (Nielsen et al, 2003). OTA biosynthesis may be influenced by eco physiological intrinsic factors, such as temperature, nitrogen shortage and pH conditions which also influence germination, growth and sporulation (Palacios-Cabrera et al, 2005;Garcia-Cela et al, 2014;Passamani et al, 2014). Under stress conditions, the signaling pathways certainly induce the production of mycotoxins (Choi et al, 2008;Kohut et al, 2009).Therefore, understanding the effects of these factors can help reduce mycotoxins, both in the field and during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, filamentous fungi grow at 25 to 35°C and 0.95 to 0.99 a w . However, for OTA production, the environmental conditions are 15 to 20°C and 0.95 to 0.98 a w (Bellí, Marín, Argilés, Ramos, & Sanchis, 2007;Palacios-Cabrera, Taniwaki, Hashimoto, & Menezes, 2005;Esteban, Abarca, Bragulat, & Cabanes, 2006;Leong, Hocking, Varelis, Giannikopoulos, & Scott, 2006;Oueslati et al, 2010;Valero, Oliván, Marín, Sanchis, & Ramos, 2007). Yeasts also grow in these conditions, thus enabling their use in biological control.…”
Section: Introductionmentioning
confidence: 99%